Aspects of Venda poetry : ( A reflection on the development of poetry from the oral tradition to the modern forms) - Milubi, Ntshavheni Alfred (My University, 1988)
Refer to the document
Thesis (Ph.D.(African Languages)) -- University of the North, 1988
Keywords: Venda poetry; Venda language; Venda poetry -- History and criticism